CONSTRAINTS OF PROJECT MANAGEMENT IN THE NIGERIAN CONSTRUCTION INDUSTRY (Journal of Engineering Studies and Research, 2024)
This study addresses the various challenges causing the ineffective practice of project management in Nigeria and proffered possible and workable solutions to them. Data were sourced from construction professionals across Nigeria and 71 responses were obtained from the 109 questionnaires that were administered. After applying the Relative Importance Index and Severity Index methods, it was established that the rankings of the critical factors that hamper contract job completion were significantly different, thus underscoring their respective importance. The recommendations, therefore, emphasized training programs, standard regulation protocol, and effective government policy to ensure effective project delivery in the Nigerian construction industry.
Keywords: relative importance index, severity index, critical factors, construction industry